Prevalence, treatment, and attributed mortality of elevated blood pressure among a nationwide population-based cohort of stroke survivors in China - Wang, Bin; Bai, Xueke; Yang, Yang; Cui, Jianlan; Song, Lijuan; Liu, Jiamin; Lu, Jiapeng; Cai, Jun (Frontiers in Cardiovascular Medicine, 2022)
Background: Elevated blood pressure (BP) is associated with substantial morbidity and mortality in stroke survivors. China has the highest prevalence of stroke survivors and accounts for one-third of stroke-related deaths worldwide. We aimed to describe the prevalence and treatment of elevated Blood Pressure (BP) across age, sex, and region, and assess the mortality attributable to elevated BP among stroke survivors in China. Methods: Based on 3,820,651 participants aged 35-75 years from all 31 provinces in mainland China recruited from September 2014 to September 2020, we assessed the prevalence and treatment of elevated BP (systolic BP ≥140 mmHg or diastolic BP ≥90 mmHg) among those with self-reported stroke and stratified by age group, sex, and geographic region. We estimated the age- and sex-specific population attributable fractions of death from elevated BP. Results: Among 91,406 stroke survivors, the mean (SD) age was 62 (8) years, and 49.0% were male. The median (IQR) stroke duration was 4 (2, 7) years. The prevalence of elevated BP was 61.3% overall, and increased with age (from 47.5% aged 35–44 years to 64.6% aged 65–75 years). The increment of prevalence was larger in female patients than male patients. Elevated BP was more prevalent in northeast (66.8%) and less in south (54.3%) China. Treatment rate among patients with elevated BP was 38.1%, and rates were low across all age groups, sexes, and regions. Elevated BP accounted for 31% and 19% of cardiovascular and all-cause mortality among stroke survivors, respectively. The proportion exceeded 50% for cardiovascular mortality among patients aged 35–54 years. Conclusions: In this nationwide cohort of stroke survivors from China, elevated BP and its non-treatment were highly prevalent across all age groups, sex, and regions. Elevated BP accounted for nearly one-third cardiovascular mortality in stroke survivors, and particularly higher in young and middle-aged patients. National strategies targeting elevated BP are warranted to address the high stroke burden in China.